2014
DOI: 10.5664/jcsm.3614
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of BMI, AHI, and Apolipoprotein E ε4 (APOE-ε4) Alleles among Sleep Apnea Patients with Different Skeletal Classifications

Abstract: OSA patients with Class II convex profile were more likely to have a lower BMI than those in other skeletal groups. In fact 20% of them were not obese, suggesting that a Class II convex profile may influence or be associated with OSA development independent of BMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…No relationship was found between the genotypes and age, BMI, total cholesterol, HDL, neck circumference, AHI, ESS, smoking, daytime sleepiness, hypertension, and coronary artery disease in our study. In one study, the mean BMI and AHI were compared among individuals who had one or more ApoE-ε4 alleles and who did not have any alleles, and similar with our findings, no difference was determined between the groups (28). In another study, increased AHI was observed in patients with OSAS with ε3/ε4 genotypes.…”
Section: Discussionsupporting
confidence: 60%
“…No relationship was found between the genotypes and age, BMI, total cholesterol, HDL, neck circumference, AHI, ESS, smoking, daytime sleepiness, hypertension, and coronary artery disease in our study. In one study, the mean BMI and AHI were compared among individuals who had one or more ApoE-ε4 alleles and who did not have any alleles, and similar with our findings, no difference was determined between the groups (28). In another study, increased AHI was observed in patients with OSAS with ε3/ε4 genotypes.…”
Section: Discussionsupporting
confidence: 60%
“…Since Angle reported a narrowed upper airway in children with Class II dentofacial deformity in 1907 [ 1 ], many studies have demonstrated that certain craniofacial patterns are related with a smaller size of the upper airway, including deficient mandible, and steep mandibular plane [ 2 4 ]. Individuals with Class II deformity and steep mandibular plane possess a smaller airway, and are higher risks for obstructive sleep apnea (OSA), especially Asians [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this report, the contribution and association of sequence variants of several OSA candidate genes [15][16][17][18][19][20] was tested in Brazilian OSA cases. None of these variants was significantly associated with OSA phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…There was no association of the APOE-ε4 allele with facial profile among these patients with OSA. However, the authors cautioned that in relation to genetic research, this study was underpowered due to the small sample size 18 .…”
Section: Discussionmentioning
confidence: 99%